2017
DOI: 10.1002/pbc.26556
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological effects of anthracyclines in adult survivors of pediatric malignancy

Abstract: Among adult survivors of pediatric cancer treated with anthracyclines, prolongation of the QTc interval was associated with subsequent LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…Drug-induced QTc interval prolongation has been considered to be a critical risk factor for cardiac toxicity and probably leads to palpitations, syncope, and sudden cardiac death caused by severe ventricular arrhythmias [30; 33; 34]. With a follow-up study of cardiac function in 147 adult surviving patients who had previously suffered from childhood tumors and received anthracycline chemotherapy, Markman TM et al found that the prolonged QTc interval was related to the subsequent development of left ventricular dysfunction [14], suggesting that the QTc interval might be an earlier indicator for evaluating the impairment of cardiac function than LVEF. The normal range of the QTc interval is 350-450 ms in adult males and 360-460 ms in adult females [33].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced QTc interval prolongation has been considered to be a critical risk factor for cardiac toxicity and probably leads to palpitations, syncope, and sudden cardiac death caused by severe ventricular arrhythmias [30; 33; 34]. With a follow-up study of cardiac function in 147 adult surviving patients who had previously suffered from childhood tumors and received anthracycline chemotherapy, Markman TM et al found that the prolonged QTc interval was related to the subsequent development of left ventricular dysfunction [14], suggesting that the QTc interval might be an earlier indicator for evaluating the impairment of cardiac function than LVEF. The normal range of the QTc interval is 350-450 ms in adult males and 360-460 ms in adult females [33].…”
Section: Discussionmentioning
confidence: 99%
“…Two ECG endpoints were pre-specified: the sum of absolute QRS amplitudes in the 6 limb leads (ΣQRS(6 L)) and the corrected QT (QTc) interval. These endpoints were chosen based on preliminary data from previously published work [8,9,11]. Amplitudes were measured in millivolts (mV) from peak to trough of the QRS.…”
Section: Ecg Evaluationmentioning
confidence: 99%
“…Additionally, ECGs are inexpensive and technically straightforward to obtain. Preliminary studies have evaluated ECG changes after anthracycline exposure; however, these changes have not been extensively studied in larger or primarily pediatric cohorts [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In their current study, Markman et al . performed exploratory analyses to determine whether electrocardiographic abnormalities might help predict which anthracycline‐treated childhood cancer survivors will go on to develop left ventricular (LV) systolic dysfunction.…”
mentioning
confidence: 99%
“…In their current study, Markman et al 4 performed exploratory analyses to determine whether electrocardiographic abnormalities might help predict which anthracycline-treated childhood cancer survivors will go on to develop left ventricular (LV) systolic dysfunction. This is the first such study to attempt to explore this question using prospective analyses, that is, accounting for the temporality of events, albeit In their cohort study, the authors reviewed their institution's clinic records for adult survivors of childhood cancer who after finishing therapy that included anthracyclines had at least one electrocardiogram prior to having at least one echocardiogram.…”
mentioning
confidence: 99%